High DMBT1 concentrations in breast milk correlate with increased risk of infection in preterm and term neonates - Ronellenfitsch Sebastian; Weiß Christel; Frommhold David; Koch Lutz; Mollenhauer Jan; Poeschl Johannes; Müller Hanna (BMC, 2012)
Abstract Background Human milk contains immune molecules involved in the protection of newborns against infections. We analyzed the concentration of Deleted in Malignant Brain Tumors 1 (DMBT1), a protein with functions in innate immunity, in breast milk. Methods DMBT1 was detected in breast milk by Western blotting and its concentration was quantified by ELISA in 95 breast milk samples collected from mothers of preterm and term neonates during the first four weeks after delivery. Possible effects of maternal or neonatal parameters were analyzed by different statistical tests. Results The mean DMBT1 concentration (± standard error of the mean) in the tested milk samples was 2.48 ± 0.26 μg/mL (range: 0.112 μg/mL to 17.984 μg/mL) and represented 0.0087% of the total protein content. The comparison between the newborns with infection and the newborns without infection revealed significantly higher DMBT1 concentrations in breast milk in the group with infection (6.72 ± 2.53 μg/mL versus 2.20 ± 0.35 μg/mL (P = 0.031)). Neither maternal nor neonatal parameters showed a correlation with the milk DMBT1 levels. Conclusions DMBT1 is a component of breast milk after birth and is up-regulated in the breast milk from mothers with newborns suffering from neonatal infection. Thus, breast milk DMBT1 may be part of the innate immunity similar to secretory IgA.